Critical language pedagogy. (January 2022) - Crookes, Graham V.
Abstract : There are long and diverse strands of thinking about how schools and schooling, teaching, curriculum, and learning could be conceptualized and developed so as to foster what is often loosely called social justice. Many of these strands go back (in Europe) at least to the French Revolution. The original term that encompasses this area is 'radical pedagogy' (that is to say, a pedagogy suitable for radicals or radical purposes; cf. Crookes, 2009). Emerging out of this area in the post-World War Two era, one version of this thought and practice that has become somewhat influential in language teaching is 'critical pedagogy', and 'critical language pedagogy' (CLP) is a key term used to refer to applications of the concepts of critical pedagogy to second language (L2) contexts.